The Unfreezing Phase in Organizational Change Management: Case: The WE-Project in Wärtsilä Finland Ltd. - Hirvonen, Päivi (My University, 2004)
To survive in a continuously changing business environment, organizations and corporations need to change. Whether the reason for change is an external pushing factor or an internal pulling factor, the change has to be managed. The aim of the study is to find out how change management’s unfreezing phase is accomplished. My purpose is to study what is change leadership in practice. In the study I try to find a way to manage a people-oriented change from the beginning to implementation. The third focus is knowledge management and how managers can lead the learning and knowledge in the unfreezing phase. The main research method is quantitative. The background and theory basis for the empirical research was made by means of an analysis of the literature concerning the phenomenon. In the theory part change management is first dealt with in general. Secondly the focus is laid on the unfreezing phase and on change resisters, effective communication and motivating subordinates. In the empirical part the unfreezing phase was studied more closely in one change project. The research object is the WE-project in Wärtsilä Finland Ltd., where a new business solution system is implemented. In the empirical study I carried out inquiries for end-users in seven divisions concerning change management activities in the WE-project. The quantitative data was analysed using the SPSS statistical program. The study exposed three main areas in change management, which were not dealt optimally in the Wärtsilä case. The outcome was that there was a need for more information and more open and better communication. In the answers also came up the lack of training in the unfreezing phase and end-users’ lack of motivation to change. The problems are quite common in the area of people-oriented changes, when comparing them to examples in the change management discussion. The results of the study highlighted also the importance of an adequate leader in change. The leader has a main role in supporting individuals in learning.
Keywords: Change management; unfreezing; communication; motivation; SAP; fi=Johtaminen ja organisaatiot|en=Management and Organization|